Determinants of the sense of efficacy of physical education teachers in higher education institutions in National Capital Region - Mariano, Janet S. (Animo Repository, 2013)
The main purpose of this study is to examine the determinants of physical education teachers' sense of efficacy using a set of variables including age, gender, educational attainment, teaching experience, verbal persuasion and mastery experience. The researcher utilized TSES questionnaire by Hoy and the researcher-made questionnaire. The questionnaires were distributed to 50 higher education institutions in the National Capital Region during the school year 2011-2012. Analysis of data reveals that years of teaching experience, verbal persuasion, and mastery experience ae significant determinants of physical education teachers' sense of efficacy.